Investigating the Role of Social Functions of Parks on Adherence to Physical Activity of Elderly People During an Epidemic Disease (COVID-19) - Azimkhani, Amin; Honari, Habib; Türkmen, Mutlu; Gholamian, Javad; Saatchian, Vahid; Salari, Reyhane (Progress in Nutrition, 2021)
Introduction: The importance of desirable physical activity as a deterrent and risk factor for the elderly is well known. The present study was conducted to investigate the role of parks' social functions on adherence to physical activity in elderly people in Mashhad During epidemic disease (COVID-19). Method: This cross-sectional study was performed using a structured interview technique and a multi-part questionnaire on 100 elderly people. Sampling was done in two stages using a systematic random method. Results: Based on the results, it was found that there is a positive and significant relationship between the social function of parks and its components with adherence to physical activity in the elderly (P